Physiological Parameters and Yield Characters of Ginger Genotypes (Zingiber officinale Rosc.) under Coconut Ecosystem - K. S., Sangeetha; Subramanian, S.; Marthandan, V. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at Coconut Nursery, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore during the period from 2012 to 2013 to study the physiological parameters and yield performance of ginger genotypes under coconut ecosystem. The experiment consisted of thirty ginger genotypes viz., ZO 1 to ZO 30 collected from different parts of India were grown as an intercrop in coconut palmsunder Coimbatore condition as treatments replicated three times in a Randomized Block Design. The genotypes were analyzed for leaf area, leaf area index, crop growth rate, relative growth rate, net assimilation rate and fresh rhizome yield of plant-1, plot-1 (1.13 m2) and estimated hectare yield at 180 and 240 DAP. The results showed the supremacy of the genotype Z0 26 (Idukki 1) over the other genotypes, as ZO 26 showed increment in leaf area (2378.72 cm2) and leaf area index (3.52) at 150 DAP and yield plant-1 (175.26 and 179.42 g), yield plot-1 (3.21 and 3.22 kg 1.13 m2) and estimated yield ha-1 (28.52 and 28.62 t ha-1) at 180 and 240 DAP, followed by the genotype ZO 28 which recorded yield plant-1 (160.72 and 162.00 g), yield plot-1 (3.17 and 3.18 kg-1 1.13 m2) and estimated yield ha (28.15 and 28.27 t ha-1) at 180 and 240 DAP. On the basis of good performance ZO 26 is adjudged as the suitable ginger genotype under coconut shade conditions.